Genetic association of lipids and lipid-lowering drug target genes with breast cancer - Tianhua Wang; Yan Yao; Xinhai Gao; Hao Luan; Xue Wang; Lijuan Liu; Changgang Sun (Discover Oncology)
Abstract Background Although several preclinical and epidemiological studies have shown that blood lipids and lipid-lowering drugs can reduce the risk of breast cancer, this finding remains controversial. This study aimed to explore the causal relationship between dyslipidemia,lipid-lowering drugs, and breast cancer. We also aimed to evaluate the potential impact of lipid-lowering drug targets on breast cancer. Method Data of 431 lipid- and lipid-related phenotypes were obtained from genome-wide association study (GWAS), and mendelian randomization (MR) analyses were performed using two independent breast cancer datasets as endpoints. Genetic variants associated with genes encoding lipid-lowering drug targets were extracted from the Global Lipid Genetics Consortium. Expression quantitative trait loci data in relevant tissues were used to further validate lipid-lowering drug targets that reached significance and combined with bioinformatics approaches for molecular expression and prognostic exploration. Further mediation analyses were performed to explore potential mediators. Result In two independent datasets, phosphatidylcholine (18:1_0:0 levels) was associated with breast cancer risk (discovery: odds ratio (OR) = 1.255 [95% confidence interval (CI) 1.120–1.406]; p = 8.936 × 10–5, replication: OR = 1.016 [95% CI, 1.003–1.030]; p = 0.017), HMG- CoA reductase (HMGCR) inhibition was genetically modeled and associated with a reduced risk of breast cancer (discovery: OR = 0.833 [95% CI 0.752–0.923], p = 5.12 × 10–4; replication: OR = 0.975 [95% CI 0.960–0.990], p = 1.65 × 10–3). There was a significant MR correlation between HMGCR expression in whole blood and breast cancer (OR = 1.11 [95% 1.01–1.22] p = 0.04). Bioinformatics analysis revealed that HMGCR expression higher in breast cancer tissues than in normal tissues, along with poor overall survival and relapse-free survival, and was associated with multiple immune cell infiltration. Finally, the mediation analysis showed that HMGCR inhibitors affected breast cancer through different immune cell phenotypes and C-reactive protein levels. Conclusion In this study, we found for the first time that phosphatidylcholine (18:1_0:0) levels are associated with breast cancer risk. We found that HMGCR inhibitors are associated with a reduced risk of breast cancer, and part of their action may be through pathways other than lipid-lowering, including modulation of immune function and reduction of inflammation represented by C-reactive protein levels.